A new pedagogical model for adventure in the curriculum: part two – outlining the model. (1st November 2016) - Williams, Andy; Wainwright, Nalda
Abstract : Background : This paper is part two of a discussion about a new pedagogical model for adventure in the curriculum. It builds upon part one, the advocacy paper, which considered important theoretical foundations, historical influences and research outcomes of outdoor adventure education (OAE) in the UK. Purpose : This paper outlines how a model for OAE might be implemented in practice in schools in the UK. Four non-negotiable features of a pedagogical model for OAE are identified as essential for pupils to gain maximum benefit from their outdoor adventure experiences. Consideration is also given to other essential features of models-based approaches to physical education that teachers need to consider to underpin the model's authenticity, including pupils' readiness for learning, teacher expertise and knowledge, and assessment and future model validation. Conclusions : Four non-negotiable features of a model for OAE are identified as being mainly outdoors, experiential learning, challenge by choice and managed risk. Key concerns arising from the implementation of these non-negotiable features are considered. These include encouraging pupils to take more responsibility for their own learning, developing closer links between school OAE and local opportunities, supporting teachers in making judgements about pupils managing their own risk, developing teachers' expertise in reviewing and developing assessment tools that measure pupils' affective learning.